Edentulism in High Poverty Rural Counties. Issue 1 (22nd October 2012) - Mitchell, Jordan; Bennett, Kevin; Brock‐Martin, Amy
Abstract Purpose: To examine the differences in oral health status among residents of high‐poverty counties, as compared to residents of other rural or urban counties, specifically on the prevalence of edentulism. Methods: We used the 2005 Behavioral Risk Factor Surveillance System (BRFSS) and the 2006 Area Resource File (ARF). All analyses were conducted with SAS and SAS‐callable SUDAAN, in order to account for weighting and the complex sample design. Findings: Characteristics significantly related to edentulism include: geographic location, gender, race, age, health status, employment, insurance, not having a usual source of care, education, marital status, presence of chronic disease, having an English interview, not deferring care due to cost, income, and dentist saturation within the county. Conclusions: Significant associations between high‐poverty rural and other rural counties and edentulism were found, and other socioeconomic and health status indicators remain strong predictors of edentulism.